2018
DOI: 10.21608/zvjz.2018.14382
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnosis of Foot and Mouth Disease Virus in Cattle with Reference to Hematological and Biochemical Changes

Abstract: The present study was carried out to clarify the effect of Foot and Mouth Disease Virus (FMDV) on cattle of different ages with references to studying the hematological parameters, biochemical aspects and cardiac biomarkers after accurate diagnosis of FMDV by reverse transcriptionpolymerase chain reaction (RT-PCR). Forty-five native breed Egyptian female non pregnant cattle (1-5 years old) were divided into two main groups. Group (1): 15 apparently healthy cattle as control group. This group includes animals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
0
1
Order By: Relevance
“…The serum biochemistry showed no significant change in total protein, albumin, and A: G ratio. This is in contrast to a significant decrease in serum total proteins observed after natural infection in the previous studies [11][12][13]. Furthermore, liver function was not affected as evidenced by unaltered AST, ALT, and GGT levels.…”
Section: Discussioncontrasting
confidence: 78%
“…The serum biochemistry showed no significant change in total protein, albumin, and A: G ratio. This is in contrast to a significant decrease in serum total proteins observed after natural infection in the previous studies [11][12][13]. Furthermore, liver function was not affected as evidenced by unaltered AST, ALT, and GGT levels.…”
Section: Discussioncontrasting
confidence: 78%
“…Neutrophilia, an increase in neutrophils in the seven samples was another indication that was the most visible and distinctive in this study. This is in line with study by Hashem et al (2018), which found significant differences in the presence of leukocytosis, neutrophilia, and monocytosis in cattle infected with FMD. The increase in phagocytic cells (neutrophils and monocytes) can be caused by tissue damage due to viral infection because neutrophils and other phagocytic cells are the first line of defense against bacterial and viral infections (Hashem et al, 2018;Kristanto and Septiyani, 2023).…”
Section: Jurnal Medik Veterinersupporting
confidence: 92%
“…This is in line with study by Hashem et al (2018), which found significant differences in the presence of leukocytosis, neutrophilia, and monocytosis in cattle infected with FMD. The increase in phagocytic cells (neutrophils and monocytes) can be caused by tissue damage due to viral infection because neutrophils and other phagocytic cells are the first line of defense against bacterial and viral infections (Hashem et al, 2018;Kristanto and Septiyani, 2023). According to Brooks et al (2022), neutrophilia can occur due to chronic inflammatory stimulation when granulocytic hyperplasia in the bone marrow occurs.…”
Section: Jurnal Medik Veterinersupporting
confidence: 92%